Total edentulous prosthesis using hybrid restorations - Alexandru Daniel Referendaru; Horia Mihail Barbu; Raluca Monica Comăneanu; Anca Iuliana Popescu (Amaltea Medical Publishing House, 2020)
Purpose. The increasing frequency of using prosthetic restorations with implant aggregation confirms the great interest of patients in the application of modern dental therapies to restore the functions of the dento-maxillary apparatus, lost as a result of edentations. Case presentation. Patient D.D., aged 63, approached our clinic for consultation and the establishment of a specialized treatment. At the clinical and radiological examination we found the presence of a total maxillary edentation and a Kennedy class I edentation with a change in the lower arch, with all the remaining teeth with indication of extraction. Following the consultation carried out together with the dentist, we proposed to the patient a treatment plan that involved bimaxillary prosthesis on implants. Conclusions. Prosthetic restorations with implant aggregation offer patients with total edentations the possibility to recover the functions of the dento-maxillary apparatus at a higher level than traditional prostheses. Hybrid prosthesis with aggregation on zygomatic and pterygoid implants allows the reduction of the treatment duration and the decrease of the costs, in the conditions of maintaining a high therapeutic predictability.